- Efektifitas Antara Metode Peer Group dan Think, Pair, Share terhadap Pengetahuan dan Perilaku Pencegahan Anemia Remaja - Yuli Astuti; Arum Margi Kusumawardhani (LPPM Hang Tuah Pekanbaru, 2023)
Background Anemia in adolescents is a health problem that receives special attention. 16% of 50 adolescents have anemia. Anemia in adolescents is caused by iron deficiency, so adolescents need to receive sufficient education and information to change their knowledge and behavior in preventing anemia. The objective of this study was to determine the effectiveness of the peer group educational method compared to the think, pair, share game method. Methods This research was an analytical experimental research method, namely research that explains the relationship/influence between variables through hypothesis testing with data collection techniques were primary data with questionnaires distributed to 80 respondents who were members of FORPIS PMI Klaten. Sampling technique was total sampling. The statistical test used was path analysis with the SPSS 23 application. Results of this study showed that the effect of providing education with the peer group method stated that there was no effect on increasing knowledge and behavior to prevent anemia in adolescents (P>0.005); and the think, pair, share card game method stated that there was an effect on increasing knowledge and behavior to prevent anemia in adolescents (P<0.005). The conclusion of this study is that the think, pair, share card game education method is more effective in increasing knowledge and behavior to prevent anemia in adolescents.